Floods and reservoir safety (ICE Publishing, 2015)
This fourth edition of 'Floods and Reservoir Safety' provides authoritative guidance on flood protection standards, flood magnitude and freeboard-guidance which is essential for engineers who are responsible for the design and inspection of reservoirs.